Dari Klik ke Kontrak: Pertimbangan Hukum dalam Perjanjian Jual Beli Online - Hastia Hastia; Andi Azizah (Indonesian Civil Law Review, 2025)
The development of digital technology has changed the way buying and selling transactions are carried out, from a conventional system to an online-based one. This phenomenon poses new challenges in legal aspects, especially related to the validity of electronic contracts, consumer protection, and the responsibility of platforms as intermediaries. This study aims to analyze online buying and selling agreements within the framework of positive Indonesian law through a normative juridical approach. Data sources are obtained from national regulations such as the Civil Code, the ITE Law, the Consumer Protection Law, and Ministerial Regulations related to e-commerce. The results of the study show that online buying and selling agreements meet the elements of the validity of the agreement as stipulated in Article 1320 of the Civil Code, as long as there is a halal agreement, skill, object, and causa. However, challenges arise in proving the identity of the parties and the validity of digital documents. On the other hand, e-commerce platforms play an important role as transaction system providers, but their legal responsibilities are still limited. Regulatory updates that are more adaptive to digital dynamics are needed, as well as increased consumer protection in electronic transactions. This study recommends the establishment of special norms related to digital contracts and intermediary responsibilities in the Indonesian legal system.